Comparison of biomaterial delivery vehicles for improving acute retention of stem cells in the infarcted heart. - O'BRIEN, FERGAL (My University, 2014)
Cell delivery to the infarcted heart has emerged as a promising therapy, but is limited by very low acute retention and engraftment of cells. The objective of this study was to compare a panel of biomaterials to evaluate if acute retention can be improved with a biomaterial carrier. Cells were quantified post-implantation in a rat myocardial infarct model in five groups (n = 7-8); saline injection (current clinical standard), two injectable hydrogels (alginate, chitosan/β-glycerophosphate (chitosan/ß-GP)) and two epicardial patches (alginate, collagen). Human mesenchymal stem cells (hMSCs) were delivered to the infarct border zone with each biomaterial. At 24 h, retained cells were quantified by fluorescence. All biomaterials produced superior fluorescence to saline control, with approximately 8- and 14-fold increases with alginate and chitosan/β-GP injectables, and 47 and 59-fold increases achieved with collagen and alginate patches, respectively. Immunohistochemical analysis qualitatively confirmed these findings. All four biomaterials retained 50-60% of cells that were present immediately following transplantation, compared to 10% for the saline control. In conclusion, all four biomaterials were demonstrated to more efficiently deliver and retain cells when compared to a saline control. Biomaterial-based delivery approaches show promise for future development of efficient in vivo delivery techniques.
PUBLISHED
Keywords: Alginate